Đáp án: (4;1) hoặc (1;1)
Giải thích các bước giải:
$\begin{array}{l}
{x^2} + 4\sqrt {3 - 3y} + 4y = 5x + 3x\sqrt {y - 1} \\
DKXD:\,\left\{ \begin{array}{l}
3 - 3y \ge 0\\
y - 1 \ge 0
\end{array} \right. \Rightarrow \left\{ \begin{array}{l}
y \le 1\\
y \ge 1
\end{array} \right. \Rightarrow y = 1\\
thay\,y = 1\,vao\,pt\,ta\,co:\\
{x^2} + 4 = 5x\\
\Rightarrow {x^2} - 5x + 4 = 0\\
\Rightarrow {x^2} - 4x - x + 4 = 0\\
\Rightarrow \left( {x - 4} \right)\left( {x - 1} \right) = 0\\
\Rightarrow \left[ \begin{array}{l}
x = 4\\
x = 1
\end{array} \right.\\
Vay\,\left( {x;y} \right) = \left( {4;1} \right)hoac\,\left( {1;1} \right)
\end{array}$